Evaluation of enamel remineralizing potential of self-assembling peptide P11-4 on artificially induced enamel lesions in vitro - Vemulapalli Sindhura; K S Uloopi; C Vinay; Rayala Chandrasekhar (Wolters Kluwer Medknow Publications, 2018)
Purpose: The purpose of this study was to evaluate the remineralizing efficacy of self-assembling peptide (SAP) P11-4 qualitatively and quantitatively using scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX), respectively. Methodology: Enamel samples (n = 24) were prepared by sectioning extracted premolars and subjected for demineralization to create artificial enamel lesions. The structural and elemental concentrations (calcium and phosphate weight %) were assessed to obtain baseline data using SEM and EDX spectroscopy, respectively. The samples were randomly allocated into two groups and were treated with SAP P11-4 (test group) and casein phosphopeptides-amorphous calcium phosphate (CPP-ACP) (control group) followed by storage in artificial saliva to evaluate the remineralizing efficacy at 1-week, 1-month, and 3-month intervals. Results: Data were analyzed using the ANOVA and unpaired t-test. From the observed results, CPP-ACP showed a significant increase in Ca: P ratio (2.04 ± 0.2) with irregular surface calcific deposition at 1-week interval and this reduced with time (1.87 ± 0.11 at 3-month interval). Whereas P11-4 showed a significant increase in Ca: P ratio (1.95 ± 0.10) with uniform ion deposition suggestive of hydroxyapatite nucleation over a 3-month period. Conclusion: SAP P11-4 exhibited superior remineralization with uniform mineral deposition compared to CPP-ACP at 3-month interval.